Output Regulation and Function Optimization of Mitochondria in Eukaryotes - Zeng, Miaolin; He, Yu; Du, Haixia; Yang, Jiehong; Wan, Haitong (Frontiers in Cell and Developmental Biology, 2020)
The emergence of endosymbiosis between aerobic alpha-proteobacterium and anaerobic eukaryotic cell precursors opened the chapter of eukaryotic evolution. Multiple functions of mitochondria originated from the ancient precursors of mitochondria and underwent remodeling in eukaryotic cells. Due to the dependence on mitochondrial functions, eukaryotic cells need to constantly adjust mitochondrial output based on energy demand and cellular stress. Meanwhile, eukaryotes conduct the metabolic cooperation between different cells through the involvement of mitochondria. Under some conditions, mitochondria might also be transferred to nearby cells to provide a protective mechanism. However, the endosymbiont relationship determines the existence of various types of mitochondrial injury, such as proteotoxic stress, mutational meltdown, oxidative injure, and immune activation caused by released mitochondrial contents. Eukaryotes have a repertoire of mitochondrial optimization processes, including various mitochondrial quality-control proteins, regulation of mitochondrial dynamics and activation of mitochondrial autophagy. When these quality-control processes fail, eukaryotic cells can activate apoptosis to intercept uncontrolled cell death, thereby minimizing the damage to extracellular tissue. In this review, we describe the intracellular and extracellular context-based regulation of mitochondrial output in eukaryotic cells, and review the emerging knowledge about multifaceted quality-control processes to deal with mitochondrial defects.